Blockchain Technology and Energy Consumption: A Comprehensive Analysis and Sustainability Considerations - Amr Elsayed; aylin erdogdu; sara elsayed (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Blockchain technology has emerged as a revolutionary force in various industries, providing unmatched transparency and security in data management. But besides its increase, there have been concerns about high energy consumption associated with blockchain operations mainly due to energy-intensive design methods This paper will effectively address these concerns with energy-saving features analyzing the use of blockchain and proposing solutions to reduce its impact on the environment Efforts This study includes an in-depth case study of Bitcoin dynamics of application that focuses on the scope of the issue. It also examines the status of current research in this area, identifying key findings and features, and emphasizing the need for urgent action.To address the blockchain resource consumption challenge, the paper explores alternative conceptualization techniques such as proof of stake (PoS) and delegated proof of stake (DPoS) and examines the role of resource generation no new and energy-efficient hardware and mining practices Sustainable One is the main theme, which advocates the integration of blockchain with environmentally friendly practices and offers possible solutions to create a blockchain environment our more ecologically sensitive surroundings. The paper draws on successful case studies to provide valuable insights and best practices for sustainable blockchain development. In conclusion, it summarizes the main findings and offers a call to action, hoping for a future where blockchain technology coexists with a sustainable and environmentally friendly world .